Epigenetic clocks and allostatic load reveal potential sex-specific drivers of biological ageing - Layte, Richard; Bourke, Nollaig; Mc Crory, Cathal; Kenny, Rose; Ni Cheallaigh, Cliona (My University, 2019)
Allostatic load (AL) and epigenetic clocks both attempt to characterize the accelerated aging of biological systems, but at present it is unclear whether these measures are complementary or distinct. This study examines the cross-sectional association of AL with epigenetic age acceleration (EAA) in a subsample of 490 community-dwelling older adults participating in The Irish Longitudinal study on Aging (TILDA). A battery of 14 biomarkers representing the activity of four different physiological systems: immunological, cardiovascular, metabolic, renal, was used to construct the AL score. DNA methylation age was computed according to the algorithms described by Horvath, Hannum, and Levine allowing for estimation of whether an individual is experiencing accelerated or decelerated aging. Horvath, Hannum, and Levine EAA correlated 0.05, 0.03, and 0.21 with AL, respectively. Disaggregation by sex revealed that AL was more strongly associated with EAA in men compared with women as assessed using Horvath’s clock. Metabolic dysregulation was a strong driver of EAA in men as assessed using Horvath and Levine’s clock, while metabolic and cardiovascular dysregulation were associated with EAA in women using Levine’s clock. Results indicate that AL and the epigenetic clocks are measuring different age-related variance and implicate sex-specific drivers of biological aging.
PUBLISHED
Keywords: Biology of aging, Biomarkers, DNA methylation; Ageing; Inclusive Society